A centralised Transmission Tree Scheduling algorithm for IEEE 802.16 mesh networks. (25th May 2012) - Cheng, Rung–Shiang; Lin, Whe Dar
Rapid advances in the mobile communications and wireless technology fields in recent decades have prompted a move away from traditional cable– and optical–based networks towards broadband wireless networks. The broadband wireless access of IEEE 802.16 protocol, therefore, introduces an important issue for bandwidth usage of Subscriber Stations (SSs) in Wireless Metropolitan Area Network. This paper proposes a centralised Transmission Tree Scheduling (nTTS) algorithm for IEEE 802.16 mesh networks. The proposed algorithm takes the effects of channel interference into account and is designed to improve both the Channel Utilisation Ratio (CUR) and the QoS performance of the mesh network.